Increased Self-Acceptance of Chronic Kidney Failure Clients through Family Support - Siti Nur Kholifah; Dwi Ananto Wibrata; Minarti Minarti; Suprajitno Suprajitno; Deanida Ankhofiya (Health Notions, 2022)
Chronic kidney failure is a global health problem in which prevalence is steadily increasing. Social support is a mechanism for individuals to improve their self acceptance. This study is aimed to explore the association between family support and self acceptance of clients with CKF in Surabaya, Indonesia. It was an analytic observational study adopting a cross-sectional design.  The populations were clients with CKF in Surabaya. The sample size was 140 respondents, selected by simple random sampling technique. This research consisted two variables, namely self-acceptence as dependen variable and family support as independent variable. Data were collected using questionnaire, then analyzed using Spearman correlation test. The study found that the majority of clients who suffered from CKF obtained good social support and adequate self acceptance. The statistical analysis showed p-value of 0.014, so it could be concluded that there is a correlation between family support and self acceptance. The family of CKD clients should provide support for increased activity by providing opportunities to carry out daily activities independently according to their abilitiesKeywords: chronical kidney; self acceptance; family support